Strategi Komunikasi Dakwah dalam Tafsir Fi Zilal Al-Qur’an: Perspektif Adabi-Ijtima‘I dan Haraki - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2024)
The paper aims to identify the essential methodology adopted by Sayyid Qutb in his classical work, tafsir Fi Zilal al-Qur’an and its instrumental role in projecting the strategic approaches of modern dakwah communication and outlook. His exegetical work laid out highly profound interpretation and scriptural analysis of the Qur’an and its universal values and political ideas based on cultural-linguistics and dynamic framework. The work set forth to expound socio-ethical principle of the Qur’an and its ideological postulate and implication in contemporary perspective. The study is based on qualitative approaches in the form of library and documentary survey. The data were obtained from related primary and secondary sources and analysed using descriptive, historical and analytical approaches. The finding shows that Sayyid Qutb had formulated an inclusive method of philosophical interpretation of the Qur’an that outlined his dynamic framework (haraki) of religious and ethico-legal views as its core ideological roots and basis. The pattern of thought and interpretation were influenced by this method in the development of his tafsir that underlie his socio-political outlook which is relevant in the development of modern narrative of dakwah and inter-faith dialogue. This categorically form the basis of his philosophy and idealism underlying his method that highlighted the essence of Islamic views and its contemporary relevance in modern context that bring forth the cultural dynamic of religious premises and the perenial values of tauhid.